Seroprevalence of Leptospira spp. in dairy cattle from the Huetar Norte Region in Costa Rica - Sequeira Soto, Jorge (2016)
A cross-sectional study was performed in the Huetar Norte region of Costa Rica (2010-2012) to establish seroprevalence to Leptospira spp among dairy cows. This region presents a high incidence of human infection.  It also has the largest milk production index in the country.  A total of 2375 individual samples was processed using the microscopic agglutination test (MAT), which corresponded to 36 farms belonging to the Dairy Farmers’ Cooperative Cooperativa de Productores de Leche Dos Pinos. Samples yielding a titer ˃ 1:160 were considered positive. Under that criterion a 9.13%, overall seroprevalence was obtained but titers as high as 1:5210 were observed in clinically healthy animals. Seroprevalence among farms was heterogeneous ranging from 0–25%.  The most frequently detected serovars were Pomona (15.7%); Tarassovi (16.6%), and Hebdomadis (25.8%).  A statistically significant association was detected (p<0.05) between certain serovars and farms.  Similarly, water sources used by the farms showed a statistical association (p< 0.05) with seroprevalence to Leptospira spp. (p> 0.05).  This association was not identified for the animal’s age or breed (p> 0.05).